2013
DOI: 10.1089/scd.2012.0686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a miR-31,Runx2, andSatb2Regulatory Loop on the Osteogenic Differentiation of Bone Mesenchymal Stem Cells

Abstract: Recently, a cohort of miRNAs, including miR-31, was reported to be downregulated during osteogenic induction by miR microarray analysis. It remains unclear how changes in miR-31 expression collaborate with bone transcription factors to activate the biological pathways that regulate the differentiation of bone mesenchymal stem cells (BMSCs). Here the effects of miR-31, Runx2, and Satb2 on the osteogenic differentiation of BMSCs were investigated using mimics and inhibitors of miR-31, small interfering RNA for k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 31 publications
6
142
1
Order By: Relevance
“…The reduced protein levels of SATB2 suggested that expression of miR‐31a‐5p was negatively correlated with SATB2 levels. We used TargetScan to predict the target of miR‐31a‐5p and found that miR‐31a‐5p could bind to the 3′‐untranslated region (3′UTR) of SATB2 (Figure 3g), a pluripotency transcription factor, which has been previously demonstrated (Deng, Wu et al., 2013; Ge et al., 2015). To further demonstrate whether miR‐31a‐5p regulated osteogenesis via SATB2, the osteogenic capacity of si‐SATB2 treated BMSCs was rejuvenated by miR‐31a‐5p inhibition (Figure 3h,i).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reduced protein levels of SATB2 suggested that expression of miR‐31a‐5p was negatively correlated with SATB2 levels. We used TargetScan to predict the target of miR‐31a‐5p and found that miR‐31a‐5p could bind to the 3′‐untranslated region (3′UTR) of SATB2 (Figure 3g), a pluripotency transcription factor, which has been previously demonstrated (Deng, Wu et al., 2013; Ge et al., 2015). To further demonstrate whether miR‐31a‐5p regulated osteogenesis via SATB2, the osteogenic capacity of si‐SATB2 treated BMSCs was rejuvenated by miR‐31a‐5p inhibition (Figure 3h,i).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that miR‐31a‐5p negatively regulates skeletogenesis and osteogenesis (Deng, Wu et al., 2013; Jin et al., 2016; Stepicheva, & Song, 2015; Weilner et al., 2016). Previous studies also demonstrated that decreased stemness and increased senescence are the primary causes of declines in osteogenic differentiation of BMSCs (Fehrer, & Lepperdinger, 2005; Zhou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work highlighted a Runx2/Satb2/miR-31 regulatory loop activated by BMP to play a vital function in ASC osteogenesis and bone regeneration. Having previously reported that knockdown of endogenous miR-31 in vitro significantly improved the osteogenic capacity of BM-MSCs, [152] the group went on to assess the therapeutic potential of lentivirus-miR-31-modified BM-MSCs cultured on poly(glycerol sebacate) scaffolds. [46] Results demonstrated that miR-31 inhibition could successfully enhance bone repair in the defect area.…”
Section: Osteogenesis and Bone Repairmentioning
confidence: 99%